Cellulose binding protein based generic biosensors - Kara, Ali Sinan (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: Biosensors are used in various industries. They have great importance in medicine and food industry. Quick prototype production is important for new biosensor production. In this work, a novel method for enzyme immobilization is described to make way for quick biosensor prototype production. Cellulosomes are enzyme complexes that target and degrade cellulosic materials. They utilize a Cellulose binding protein/module (CBM) to attach themselves to the cellulosic material. CBM fused enzymes are used in this work to immobilize enzymes on nanofibril cellulose (NFC) covered screen-printed electrodes. Cellulosic materials are abundant and cheap, thus making them a suitable immobilization material. It is shown in this work that enzymes can be expressed as CBM-fused chimeric proteins to create quick and reliable biosensors.

ÖZET: Biyosensörler farklı endüstrilerde sıklıkla kullanılmaktadırlar. Özellikle sağlık ve gıda endüstrisinde yaygın olarak kullanılırlar. Hızlı prototipleme, yeni biyosensörlerin üretimi için önemlidir. Bu çalısmada, hızlı biyosensör prototiplemesi için yeni bir immobilizasyon metodu denenmistir. Selülozom, selülozik materyallere bağlanan ve parçalayan bir enzim topluluğudur. Yapısında selüloza bağlanmak için bir selüloz bağlanma modülü bulundur. Bu çalısmada selüloz bağlanma modülü ile birlestirilen enzimler elektrot yüzeyleri nanofibril selüloz kaplı yüzey baskılı elektrotların üzerine immobilize edilmistir. Selülozik materyaller ucuz olmaları sebebiyle immobilizasyon için uygun materyallerdir. Bu çalısmanın sonucu olarak, enzimlerin selüloz bağlanma modülü ile birlestirilerek rekombinant üretimi ile hızlı ve güvenilir biyosensör üretiminin gerçeklestrilebilineceği gösterilmistir.
Selüloz bağlanma modülü bazlı jenerik biyosensörler
Keywords: Screen-printed Electrodes; Cellulose Binding Module; Amperometry; Biosensor; Nanofibril Cellulose; Yüzey Baskılı Elektrotlar; Selüloz Bağlanma Modülü; Amperometri; Biyosensör; Nanofibril Selüloz